Development of modified method for text recognition in standardized picture - Касьян, Константин Николаевич; Братчиков, Владимир Владимирович; Шкарупило, Вадим Викторович (Eastern-European Journal of Enterprise Technologies, 2015)
Text recognition in images is a very urgent problem in modern search engines. There are many different methods and techniques for text recognition. The paper is a method for text recognition in a standardized image. Standardized image means an image that has the same font, character size, certain writing order, such as the serial number or license plate of the car. In the paper, we developed an improved method for text recognition in the image. The method consists in a preliminary search of the same characters and memorizing their positions. Identical symbols are recognized only once. After recognition, symbols are arranged in the desired position. Image processing and isolation of character boundaries is performed using JavaCV. The modified method was developed based on the template method. Both methods were implemented in Java language. To create a text-recognition software, a neural network based on a single-layer perceptron was built. The results of tests have shown the superiority of the modified method compared to the original one. At best, the performance of the modified method is 300% of the performance of the original one. At worst, it is slower only by 5-10%. In addition, the modified algorithm requires 3 times fewer iterations. The modified algorithm allows to accelerate the text recognition process in standardized images if they have recurring characters.